Exploring Community Participation Towards Sustainable Livelihoods - Skhosana, Rebecca Mmamoagi; Nel, Hanna (Southern African Journal of Social Work and Social Development)
South Africa still struggles with poverty, inequality and unemployment after two decades of democracy. By historical and international standards, poverty levels continue to be relatively high despite some recent progress in reducing the scourge. This study explores community participation to mobilise the strengths and assets of community members towards sustainable livelihoods in Tshwane, Gauteng Province, South Africa. The qualitative study was undertaken with 21 participants from four community development projects. The participants were purposefully selected, and individual semi-structured and focus group interviews were utilised to elicit data following ethical research principles. The findings of the study demonstrate that the community development projects managed by the development centres struggle to uphold accountability in poverty alleviation because they lack community participation, skills and the capacity to mobilise assets. The implications of the study are that development centres need to ensure the participation and mobilisation of strengths and assets of community members to empower them towards self-reliant, sustainable livelihoods.